Global importance of nitrogen fixation across inland and coastal waters - Fulweiler, Robinson W; Rinehart, Shelby; Taylor, Jason; Kelly, Michelle C; Berberich, Megan E; Ray, Nicholas E; Oczkowski, Autumn; Balint, Sawyer; Benavides, Mar; Church, Matthew J; Loeks, Brianna; Newell, Silvia; et al. (Science (New York, N.Y.), 2025)
Biological nitrogen fixation is a key driver of global primary production and climate. Decades of effort have repeatedly updated nitrogen fixation estimates for terrestrial and open ocean systems, yet other aquatic systems in between have largely been ignored. Here we present an evaluation of nitrogen fixation for inland and coastal waters. We demonstrate that water column and sediment nitrogen fixation is ubiquitous across these diverse aquatic habitats, with rates ranging six orders of magnitude. We conservatively estimate that, despite accounting for less than 10% of the global surface area, inland and coastal aquatic systems fix 40 (30 to 54) teragrams of nitrogen per year, equivalent to 15% of the nitrogen fixed on land and in the open ocean. Inland systems contribute more than half of this biological nitrogen fixation.
Keywords: fixace dusíku; Nitrogen; oceány a moře; Ecosystem; Geologic Sediments; Seawater; ekosystém; Oceans and Seas; geologické sedimenty; Nitrogen Fixation; mořská voda; dusík